Estimating the costs of interrelated reproductive disorders in dairy farms - A. Wicaksono; B.H.P. van den Borne; H. Aardema; T. van Werven; H. Hogeveen; W. Steeneveld (Journal of Dairy Science, 2025)
ABSTRACT: Several reproductive disorders can occur in dairy cows from peripartum until the start of pregnancy. Their occurrence can be interrelated, which complicates the estimation of subsequent economic impact. Estimation of the economic impact of reproductive disorders is essential for dairy farmers to make informed decisions. It enables them to prioritize the prevention of disorders with the highest economic impact. The aim of this study was to estimate the costs of dairy cow reproductive disorders, including dystocia, retained placenta, acute metritis, clinical endometritis, anovulation, cystic ovarian disease (COD), and sub-estrus, taking their complex interrelations into account. An existing individual cow-based, dynamic, and stochastic bio-economic simulation model of a 200-cow-herd with daily time steps was extended to include the interrelations of the 7 reproductive disorders studied. The parameterization of the probabilities of developing reproductive disorders was based on scientific literature and expert opinion. Nine scenarios were simulated and included (1) a default scenario, in which all reproductive disorders were included in the simulation model. The second to eighth scenarios were simulated with zero probability of each specific disorder, including (2) dystocia, (3) retained placenta, (4) acute metritis, (5) clinical endometritis, (6) anovulation, (7) COD, and (8) sub-estrus. In the ninth scenario, all disorders were absent. The annual net economic return (NER) of the herd was calculated for all the scenarios. Subsequently, the NER of the scenarios with zero probability of disorder (scenarios 2–9) were compared with the NER of the default scenario and its difference was considered the cost of each specific reproductive disorder (or of all 7 reproductive disorders combined). This study showed that taking all disorders into account resulted in a mean annual cost of €20,013/herd per year or €100/cow per year. At herd level, the highest mean annual cost was observed for acute metritis (€5,908/herd per year or €30/cow per year), whereas the lowest mean annual cost was observed for dystocia (€897/herd per year or €4/cow per year). In the context of cost per case, the highest cost was observed for acute metritis (€257/case), whereas the lowest cost was observed for COD (€58/case). Given the interrelationships between reproductive disorders, preventing one disorder reduces the occurrence of others, thereby lowering their overall economic impact.